Teaching points in anesthetic management for transcatheter pulmonary valve replacement: a case series - Meng Zhang; Siyuan Song; Jing Zhuang; Tong Wang; Qiang Lyu; Qian Lei (Frontiers in Cardiovascular Medicine, 2026)
Background Transcatheter pulmonary valve replacement (TPVR) is an established minimally invasive treatment for right ventricular outflow tract dysfunction after repair of congenital heart diseases. However, anesthetic management remains challenging because of complex right-sided pathophysiology and variable hemodynamic burden. Case We retrospectively reviewed three representative single-center TPVR cases and summarized perioperative anesthetic management and early outcomes. The patients reflected distinct clinical patterns: severe RVOT obstruction with marked right ventricular pressure overload, severe pulmonary regurgitation with right ventricular volume overload, and complex adult congenital heart disease with pulmonary hypertension, atrial fibrillation, and shunt physiology. Despite these differences, anesthetic priorities were similar, including right ventricular protection, control of pulmonary vascular load, stable induction, lung-protective ventilation, close rhythm and hemodynamic monitoring, and preparation for critical procedural events. Conclusions All three patients underwent TPVR successfully with stable early postoperative recovery, highlighting the importance of individualized but goal-directed anesthetic strategies.